Comparison of Different Hydrocolloids on the Novel Development of Muffins from “Purple Yam” (Dioscorea alata) Flour in Sensory, Textural, and Nutritional Aspects - Dewni Gunasekara; Ashani Bulathgama; Indira Wickramasinghe (International Journal of Food Science)
Hydrocolloids can act as gluten substitutes to form the structural equivalents of the gluten network in gluten-free bakery products. “Purple yam” (Dioscorea alata) is one of the underutilized yams in Sri Lanka with high nutritional potential. The overall objective of this study was to develop gluten-free muffins using “Purple yam” (Dioscorea alata) flour with hydrocolloids (pectin, xanthan gum, and guar gum) and investigate the nutritional composition and selected properties of the muffins. The texture profiles of gluten-free muffins were analyzed through the following parameters: hardness, adhesiveness, cohesiveness, etc. The chromameter values were obtained and sensory evaluations for gluten-free muffins were carried out. The highest moisture content was recorded in pectin-incorporated muffins (17.70±0.50%). The protein content of all three types of muffins was around 5%. The highest fat content was recorded in pectin-incorporated muffins (19.26±0.51%). The ash content of all three types of muffins was around 2%. Potassium was the most predominant element found in each muffin. The hardness of guar gum-incorporated muffin (6379.3±135.9 g) was greater than that of the pectin-incorporated one (6082.3±23.4 g). Xanthan gum-incorporated muffins had significantly decreased cohesiveness (0.19±0.04). The highest springiness was obtained in pectin-incorporated muffin (37.13±1.61 mm). The descending order of the chewiness of muffin is pectin−added>xanthan gum−added>guar gum−added sample. According to the sensory evaluation, pectin-incorporated muffin was the best as it had obtained the highest sum of ranks for appearance, color, taste, after taste, and overall acceptability.